Analysis of the relations between scientometric and economic indicators of Russian universities’ performance - Sandler, Daniil; Gladyrev, Dmitry (Business, Management and Economics Engineering, 2020)
Purpose – The study focuses on the relationship between universities’ publication activity and such indicators of their economic performance as revenues from extrabudgetary sources and revenues from research. Research methodology – The study relies on the economic, structural and scientometric data of 49 large Russian universities in a four-year period obtained from the Monitoring of the Efficiency of Higher Education Institutions and the analytical tool SciVal. The research method is a regression analysis with panel data models. Findings – The study has brought to light some interesting relations between scientometric and economic indicators: among other things, it was shown that higher rates of internationally coauthored publications are positively related with the share of universities’ revenues from extrabudgetary sources. The rates of citation of universities’ publications in journals indexed in major international databases are positively associated with revenues from research. Interestingly, there was a negative relationship between the share of nationally co-authored and the revenue from research. Practical implications – The results can be used for the strategic management of universities and for developing national policies in the sphere of higher education and science. Originality/Value – Apart from the most frequently used scientometric indicators such as the number of publications and citations, the following indicators were also included in the analysis: the share of internationally and nationally co-authored (domestic) publications, the share of publications in economics and management, in physics, arts and humanities.